(untitled) (CIPEEX, 2025)
Obesity, recognized by the World Health Organization (WHO) as a multifactorial disease with genetic and environmental influences, represents a serious global public health issue. Its strong association with type 2 diabetes mellitus (T2DM) highlights the relevance of antidiabetic medications such as semaglutide, not only for glycemic control but also for inducing weight loss. Semaglutide, with proven efficacy in reducing body weight, has been approved for the treatment of obesity, including in individuals without T2DM. However, the increasing "off-label" use for aesthetic purposes raises significant concerns regarding the risks, adverse effects, and consequences of indiscriminate use. This is a literature review conducted through research in databases such as Google Scholar, Scielo, and PubMed, covering publications from the last eight years. Included materials were randomized clinical trials, systematic reviews, regulatory agency opinions (such as Anvisa), and medical opinion articles that addressed the use of medications like semaglutide for aesthetic purposes. The keywords used were: "semaglutide," "weight loss," "diabetes pen," and "obesity." Weight gain is intrinsically linked to a higher risk of serious comorbidities such as hypertension and T2DM, driving interest in the development of non-invasive pharmacological therapies to combat obesity. Ozempic (semaglutide), a GLP-1 receptor agonist, has demonstrated efficacy in controlling postprandial glucose metabolism and reducing body weight. It works by decreasing appetite and hunger, increasing satiety, modifying food preferences, and limiting caloric intake. The ease of access and rapid results encourage the indiscriminate use of these medications for weight loss. However, this underscores the need for nutritional monitoring and an approach focused on healthy weight loss that does not rely solely on pharmacological treatment due to potential long-term side effects. Therefore, the medication should not be considered the only solution for obesity. Adopting a healthy lifestyle, including a balanced diet and regular exercise, is essential to achieve lasting results. Semaglutide, while effective in weight loss and metabolic control, requires ethical rigor and clinical support in its use. Obesity, as a multifactorial condition with a significant impact on public health, demands interventions that go beyond isolated pharmacotherapy, requiring a multidisciplinary team for dietary re-education, promotion of physical activity, and behavioral modification. In this context, the medicalization of weight loss without proper professional follow-up can lead to long-term adverse effects and compromise the sustainability of results. Furthermore, additional research is crucial to deepen the understanding of semaglutide’s mechanisms of action and its long-term clinical impact.